Kualitas Produk Dan Harga Terhadap Minat Beli Konsumen Pada Pakaian Second Di Thrifty Culture Gorontalo - Ariawan Ariawan; Rosmina Hiola; Ni Kadek Ebiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to determine the impact of the influence of product quality and price both simultaneously and partially on consumer buying interest (Y). The analytical method used is path analysis or path analysis. Based on the results of this study, the first hypothesis proposed says that product quality (X1), price (X2) simultaneously have a significant effect on consumer buying interest (Y). With a coefficient of determination (R Square) of 0,745 (74,5%). The results for the F-count test have shown results with a value of 142,026 while the F-table is 3,089 and the probability sig is 0,000 < probability α = 0,05. The second hypothesis is that product quality (X1) has a significant effect on consumer buying interest (Y). Probability value alpha (α) (0,005 <0,05). Meanwhile, the t-count value is greater than the t-table value (2,897 > 1,984). The third hypothesis is that price (X2) has a significant effect on consumer buying interest (Y). Probability value alpha (α) (0,000 <0,05). Meanwhile, the t-count value is greater than the t-table value (4,338 > 1,984). Research has found that price dominates a significant influence on consumer buying interest, so that companies are more able to maintain prices, by increasing product quality.